2015
DOI: 10.1186/s12888-015-0454-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant/antioxidant imbalance is an inherent feature of depression

Abstract: Background50% to 60% of the people who have recovered from the first episode of depression experience a relapse. The immune system of the people suffering from depression is in a permanent state of pathological pro-inflammatory readiness. There are some reports that depressive episodes cause sensitization of immune-inflammatory pathways and that staing of depression (e.g. number of depressive episodes) is correlated with immune-inflammatory markers.The main objective of the study was to delineate whether recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 39 publications
2
10
1
Order By: Relevance
“…Oxidative stress and oxidant/antioxidant imbalance are involved in the pathophysiology of psychiatric disorders. Antidepressants mitigated the activity of oxidative stress in depressed patients [4]. The level of MDA increased in psychiatric disorders like depression [50,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress and oxidant/antioxidant imbalance are involved in the pathophysiology of psychiatric disorders. Antidepressants mitigated the activity of oxidative stress in depressed patients [4]. The level of MDA increased in psychiatric disorders like depression [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Literature has been suggested a role for oxidative stress as increasing in nitric oxide (NO) and malondialdehyde (MDA) as well as oxidant/antioxidant imbal- Lorigooini ance in the pathophysiology of psychiatric disorders like depression and anxiety [4][5][6][7]. Oxidative stress that occurs as a result of stimulating the production of free radicals, nonradical molecules, reactive oxygen, and nitrogen species is involved in depression and anxiety disorders [8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a Polish study reported that the enzyme activity of MnSOD was more decreased in patients with recurrent depressive disorders than that in a group of healthy subjects [53]. Nevertheless, no significant interrelation in the expression of this enzyme was found in both groups with the first episode of depression and with recurrent depressive disorders [54].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…A new understanding of mood disorders, including depressive disorders, has emerged over the past three decades. Depression is conceptualized as an immune-inflammatory and oxidative stress disorder associated with neuroprogressive changes as a consequence of peripherally activated immune-inflammatory pathways, including peripheral cytokines and immune cells which penetrate into the brain via the blood barrier [6,7], as well as nitro-oxidative stress and antioxidant imbalances [8,9].…”
Section: Introductionmentioning
confidence: 99%